Spatiotemporal changes in the genetic diversity of harmful algal blooms caused by the toxic dinoflagellate Alexandrium minutum. Issue 3 (20th January 2014) - Dia, A.; Guillou, L.; Mauger, S.; Bigeard, E.; Marie, D.; Valero, M.; Destombe, C.
Abstract Organisms with sexual and asexual reproductive systems benefit from both types of reproduction. Sexual recombination generates new combinations of alleles, whereas clonality favours the spread of the fittest genotype through the entire population. Therefore, the rate of sexual vs. clonal reproduction has a major influence on the demography and genetic structure of natural populations. We addressed the effect of reproductive system on populations of the dinoflagellate Alexandrium minutum. More specifically, we monitored the spatiotemporal genetic diversity during and between bloom events in two estuaries separated by 150 km for two consecutive years. An analysis of population genetic patterns using microsatellite markers revealed surprisingly high genotypic and genetic diversity. Moreover, there was significant spatial and temporal genetic differentiation during and between bloom events. Our results demonstrate that (i) interannual genetic differentiation can be very high, (ii) estuaries are partially isolated during bloom events and (iii) genetic diversity can change rapidly during a bloom event. This rapid genetic change may reflect selective effects that are nevertheless not strong enough to reduce allelic diversity. Thus, sexual reproduction and/or migration may regularly erase any genetic structure produced within estuaries during a bloom event.